2008
DOI: 10.1111/j.1744-7917.2008.00234.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of light and habitat on predation of Culex quinquefasciatus (Diptera: Culicidae) larvae by the waterbugs (Hemiptera: Heteroptera)

Abstract: The influence of light and habitat structure on the predation of Culex quinquefasciatus larvae by the common heteropteran water bug, Diplonychus (=Sphaerodema) annulatus, D. rusticus and Anisops bouvieri was assessed in the laboratory. It was revealed that water bugs predate more in presence of light than in dark conditions. While A. bouvieri consumed more prey in structured conditions, D. annulatus and D. rusticus consumed more prey in open conditions. The selection of prey size as well as the respective numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…While the paddy plants and floating detritus of varied origins are utilized by the macroinvertebrates like mosquito larvae, the predators face the difficulty in chasing the prey in refuge. Empirical estimates suggest that the habitat complexity and availability of light influence the efficacy of the insect predators against mosquito immature (Saha et al, 2008(Saha et al, , 2009. The observations on the numbers of mosquito larvae in the unit spaces reflect the effects of the light and vegetation as factors influencing the spatial distribution.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…While the paddy plants and floating detritus of varied origins are utilized by the macroinvertebrates like mosquito larvae, the predators face the difficulty in chasing the prey in refuge. Empirical estimates suggest that the habitat complexity and availability of light influence the efficacy of the insect predators against mosquito immature (Saha et al, 2008(Saha et al, , 2009. The observations on the numbers of mosquito larvae in the unit spaces reflect the effects of the light and vegetation as factors influencing the spatial distribution.…”
Section: Discussionmentioning
confidence: 96%
“…The habitat in the rice fields is complex owing to the presence of the paddy plants and physical structures including the sediment and the detritus. Often the mosquito larvae and co-occurring organisms utilize the physical structures as a refuge thereby altering the possible interactions within and between organisms (Saha et al, 2008(Saha et al, , 2009. In order to evade…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous observations have devoted much attention to the Notonectidae, which have a significant influence on the regulation of water invertebrates and even young fish and amphibians (Louarn and Cloarec, 1997;Kopp et al, 2006;Vandekerkhove et al, 2012). It has been demonstrated that they can be effective regulators of mosquitoes and help to control them, and that, if necessary, they can also feed on Chironomidae (Saha et al, 2008(Saha et al, , 2010. As shown in small water bodies, they can regulate the abundance and diversity of the entire invertebrate population (including plankton), as confirmed by experiments similar to those presented in our study (Eitam and Blaustein, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Such information can be found in only a few works (Dieguez and John, 2003;Bourkal, 2012, 2013). These, however, have focused on predation by only one Heteroptera family, the Notonectidae, mainly in the context of predation on Culicidae larvae (Dieguez and John, 2003;Eitam and Blaustein, 2004;Saha et al, 2008;Eitam and Blaustein, 2010). As water bugs are abundant in the shallow littoral of lakes (Płaska, 2012), it therefore seems that they may play an important role in shaping the qualitative and quantitative structure of zooplankton.…”
Section: Introductionmentioning
confidence: 99%